Evaluation of Surabaya MSMEs Empowerment through the Jatim Bejo Program - Sumarsono, Adelia Putri; Nafi'ah, Binti Azizatun (Department of Public Administration, 2025)
Jawa Timur Belanja Online (Jatim Bejo) program is present as an effort of the East Java Provincial Government to support the empowerment of Micro, Small, and Medium Enterprises (MSMEs) as providers through the East Java Provincial Government's goods/services procurement program in the digital era. In the digital era, MSMEs are required to adapt to information technology to increase their competitiveness. However, many MSME players still face obstacles in understanding and implementing digital technology for marketing and business operations. Although this program has been running since 2021, there is still a gap between the number of MSMEs in Surabaya and those registered in Jatim Bejo. This study examines the evaluation of MSME empowerment in Surabaya City through the Jatim Bejo program, using quantitative methods with a descriptive statistical approach. Data collection techniques were obtained from the results of distributing questionnaires to MSMEs in Surabaya as providers in Jatim Bejo with a total sample of 100 respondents, as well as conducting participatory observations related to the implementation of Jatim Bejo related to MSME empowerment efforts. The results showed that the empowerment of MSMEs in Surabaya through the Jatim Bejo program was considered to have received a positive response from respondents, with 79% of respondents stating that the Jatim Bejo program helped them in increasing product sales through Jatim Bejo.